Molecular Identification of Hyalomma Ticks and Application of Bacillus thuringiensis Toxins as an Effective Biological Acaricide - Panhwer Sana Noor; Munir Ahmed; Abdul Suboor Ansari; Javaid Ali Gadahi; Shahar Bano Memon; Mansoor Tariq; Zubair Ahmed Laghari; Feroza Soomro; Bachal Bhutto; Noor-Un-Nisa Mari; Zhengli Chen (Journal of Parasitology Research, 2024)
Bacillus thuringiensis (B. thuringiensis) is considered one of the most important entomopathogenic microorganisms. It produces potent toxins against insects. Therefore, the present study investigates the bioacaricidal properties of B. thuringiensis on the Hyalomma tick species. Firstly, we identify Hyalomma ticks based on morphological screening and molecular characterization. The cytochrome C oxidase subunit I (COX1) gene was selected for the polymerase chain reaction (PCR) analysis, which resulted in the amplification of 656 bp. The amplified products were sequenced, and the isolated (COX1) gene of ticks was submitted to the gene bank of NCBI (Accession No. OR077934.1). The nucleotide sequences were retrieved from the NCBI data bank by BLASTn analysis, which confirmed that all obtained sequences belong to genus Hyalomma, and multiple alignments confirmed that the sequence of Hyalomma anatolicum Tandojam-isolate (HA-TJ) 100% aligned with Hyalomma analoticum KP792577.1, Hyalomma detritum KP792595.1, Hyalomma excavatum KX911989.1, and H. excavatum OQ449693.1. The generated phylogenetic tree confirmed that sequences of HA-TJ COX1 clustered with a single clad of H. analoticum, H. excavatum, and H. detritum. The acaricidal effect of B. thuringiensis toxins B. thuringiensis spore crystal mix (BtSCM) and B. thuringiensis crystal proteins (Btcps) was evaluated against larvae and adult life stages of Hyalomma ticks in vitro. We applied Btcps and BtSCM separately with different concentrations and calculated the mortality percentage. Adult mortality was estimated at the 8th, 10th, 12th, and 15th days posttreatment and larval mortality after 24 h. During treatment of the adult life stage, at first, ticks were immersed in different concentrations of Btcps and BtSCM for 5 min after the treatments, and the samples were transferred to sterile containers and placed in an incubator with 80% humidity at 23°C. Furthermore, Btcps produced the highest mortality on Day 15, 89±1.00% at a concentration of 3000 μg/mL, followed by the 12th, 10th, and 8th days produced 83±1.91%, 70±1.15%, and 61±1.00%, respectively. BtSCM produced mortality of 69±1.91% on Day 15 at a concentration of 3000 μg/mL, followed by the 12th, 10th, and 8th days at 57±2.51%, 37±1.91%, and 34±2.00%. The present study revealed that B. thuringiensis toxins produced a significant (p<0.05) increase in mortality rate in adults of Hyalomma ticks. Additionally, Btcps and BtSCM were used to treat the larval stage. The treatments were applied to calculate the mortality percentage via the Laravel packet test. At a 1500 μg/mL concentration, Btcps resulted in the highest mortality of 98±1.15%; this was followed by 1250 μg/mL, 1000 μg/mL, and 750 μg/mL, which produced mortalities of 76±1.63%, 60±1.63%, and 56±1.63%, respectively. In addition, BtSCM produced a mortality rate of 79±2.51% at a concentration of 1500 μg/mL. Furthermore, 75±2.51%, 65±1.91%, and 58±1.15% mortality were observed at concentrations of 1250 μg/mL, 1000 μg/mL, and 750 μg/mL, respectively. The results showed a significant (p<0.05) increase in larval mortality compared to the control group. We conclude that B. thuringiensis toxins are applicable as a bioacaricide.